Surgical Post-acute Care Spending Driven by Choice of Post-Acute Care Setting Rather than Intensity of Services - Chen, Lena M. (Health Aff (Millwood), 2017)
Episode-based payment models are increasing in popularity for surgery. We evaluated how much variation in post-acute care (PAC) spending after surgery is explained by: PAC choice (i.e., choice of home health, outpatient rehabilitation, skilled nursing, or inpatient rehabilitation) versus PAC intensity (amount of spending in a chosen setting). PAC spending varied widely between hospitals in low versus high PAC spending quintiles (total hip replacement (THR): $5,112 to $11,708, or 129% difference; coronary bypass grafting (CABG): $4,143 to $8,403, or 103% difference; colectomy: $3,345 to $6,104, or 82% difference). This variation persisted after adjusting for PAC intensity, but diminished considerably after adjusting for choice of PAC setting (THR 109% vs. 16% difference; CABG 108% vs. 4% difference; colectomy 62% vs. 21% difference). Health systems aiming to improve surgical episode efficiency should focus on working with patients to choose the highest value PAC setting.